Metal organic framework-derived advanced porous material supported catalysts for green diesel production from palm fatty acid distillate via deoxygenation pathways - Chang, He; Lee, Hwei Voon; Yap, Taufiq Yun Hin; Abdulkareem-Alsultan, G.; Seenivasagam, Sivasangar (Elsevier Ltd, 2025)
Green diesel production from renewable non-edible feedstock through deoxygenation (DO) is a viable step to reduce dependency on petroleum-based fuel in the transportation sector. As such, the catalytic conversion of undiluted palm fatty acid distillate (PFAD) into paraffinic hydrocarbons through DO was explored using Ni-doped pyrolysed MIL-101 (MOF-Cr2O3). In this study, 4–25 wt% Ni/MOF-Cr2O3 catalysts were prepared through wet impregnation and calcined at 600 °C for 4 h under N2 flow, followed by reduction at 450 °C for 4 h under H2 flow. Catalytic DO was carried out within 280 °C–360 °C with a retention time of 1–5 h by using 1–7 wt.% of catalyst loading under continuous N2 flow. Results showed that 14Ni/MOF-Cr2O3 was the most effective catalyst for PFAD conversion into paraffinic hydrocarbons. About 93 % hydrocarbon yield with 91 % n-(C15+C17) selectivity was achieved using 3 wt% catalyst at 320 °C within 3 h. The exceptional catalytic activity was attributed to the synergistic correlation between catalyst properties, including finely dispersed Ni facilitated by a porous and high surface area support, and optimal presence of acid-base active sites on the catalyst. Preliminary studies showed that 14Ni/MOF-Cr2O3 displayed high stability in terms of catalytic activity and regeneration potential.